Restrictions on indoor and outdoor NO2 emissions to reduce disease burden for pediatric asthma in China: A modeling study - Ying Hu; John S. Ji; Bin Zhao (Elsevier, 2022)
Summary: Background: Epidemiological studies have reported the associations between nitrogen dioxide (NO2) and pediatric asthma incidence, but unable to ascertain indoor NO2 sources. We estimated the pediatric asthma incidence and corresponding economic losses attributable to NO2 from indoor and outdoor sources in urban areas in China. Methods: Exposure to NO2 from indoor and outdoor sources in 2019 were estimated separately with a source-specific model validated by measurements from different studies, and NO2 exposure after restricting emissions indoor (from cooking or second-hand smoking) and outdoor (to meet WHO interim targets and air quality guideline) were projected. Disease burden of NO2-attributable new-onset pediatric asthma were estimated based on NO2 exposure, concentration-response function from a meta-analysis, and number of pediatric asthma populations. Economic impacts were estimated based on the costs of pediatric asthma in China. Findings: In China, NO2 is associated with an estimated 637,000 (95% uncertainty interval 358,000-851,000) new pediatric asthma cases and 1,358 million (674-2145) RMB economic losses in urban areas in 2019. 296,000 (222,000-523,000) new pediatric asthma cases would be prevented each year by restricting NO2 emissions indoor, i.e., switching from using gas stoves to electic stoves for cooking. 393,000 (119,000-463,000) new pediatric asthma cases would be prevented each year when outdoor air meets the air quality guideline for NO2 (< 10 µg/m3). Interpretation: Restricting both indoor and outdoor NO2 emissions are necessary to reduce pediatric asthma incidence in urban areas. NO2 restrictions may be achieved through clean energy transition and adoption of climate change mitigation activities. Funding: Vanke School of Public Health, Tsinghua University (2021JC005).